Phase Evolution, Mechanical Properties and Corrosion Behavior of CoCrFeNi Alloys: Effect of Hf - Cengiz, Sezgin; Fazi, Andrea; Ceylan, Doğancan; Muhaffel, Faiz; Tarakçı, Gürkan; Özer, Gökhan; Thuvander, Mattias (Elsevier, 2026)
It is well known that the formation of phases and microstructures, and their interactions, must be understood to develop new alloys with excellent mechanical properties and corrosion resistance. This study aimed to investigate the effect of Hf content on the phase formation and evolution in CoCrFeNi high-entropy alloys (HEAs). The formation of micrometre and nanometre-scale phases (FCC, Laves) was studied by electron microscopy, and phase interfaces were examined using atom probe tomography (APT). With increasing Hf content, the HEAs gradually transformed from FCC single phase to firstly Ni7Hf2+FCC, and finally to lamellar FCC/Laves phases. The FCC phase shows homogeneous Co–Cr–Fe distribution, while the Laves phase is enriched in Co–Ni–Hf, with a distinct Ni–Co depletion zone forming at the FCC/Laves interface due to mixing enthalpy effects. The growing Laves fraction significantly improves hardness—up to a fourfold increase for CoCrFeNiHf0.42 alloy, while the elastic modulus rises only when the eutectic structure becomes dominant. Corrosion studies reveal a dual effect: CoCrFeNiHf0.1 improves passive film stability, whereas higher Hf contents promote second-phase formation, leading to microgalvanic corrosion and reduced corrosion resistance. Overall, Hf addition plays a compositiondependent role in tailoring microstructure, mechanical properties, and corrosion behavior of CoCrFeNi HEAs.
Keywords: Eutectic High Entropy Alloys; Laves Phase; Atom Probe Tomography; Phase Formation; Nanoindentation; Corrosion Resistance